Aesthetic study of Abolfazl Zarūī 's Rofūzehā in terms of language, meaning and music - Elham Omomi; Morteza Rashidi Ashjerdi; Mehrdad Chatraei (مطالعات زبانی و بلاغی)
This article deals with the aesthetic analysis of three important stylistic dimensions (language, meaning, and music) in Rofūzehā (The Failed Ones), the satirical poetry collection of Abolfazl Zarūī Nasrābād. Inconsistencies and defamiliarizations in the realm of humor occur in various domains and delight the audience. By applying some rules to these three stylistic dimensions, Zarūī has created inconsistencies in poetry and has thus enlivened the humor in his work. The present authors have aimed to reveal the subtleties and techniques of Zarūī's humor and extract frequent features in determining the poet's stylistic identity. The research method is descriptive-analytical and library-based. The results of the research show that he has displayed his skills in the field of language through techniques such as coinage, colloquial writing, westernization, and traditionalism. Concerning meaning, he has transformed speech by nonsensical composition, omission, revelation, and contradiction. As for music in his poetry, he has created a proportionate and coherent atmosphere for humor by breaking the usual rules of meter, rhyme, and rhythm.